Patterns of triggers, ideation and motivational factors of contraceptive utilization among women and gate-keepers in Nigeria: a scoping study on the resilient and accelerated scale up of DMPA-SC in Nigeria (RASUDIN) - Kehinde Osinowo; Michael Ekholuenetale; Oluwaseun Ojomo; Abiodun Hassan; Oladapo Alabi Ladipo (BMC, 2020)
Abstract Background Women have unfair share in the burden of unintended pregnancy outcome and unhealthy interpregnancy intervals. An understanding of the triggers, ideation and motivational factors influencing utilization of modern contraceptives is relevant for efforts aimed at increasing utilization among the general public, specifically sexually active women. The objective of this study is to explore the triggers, ideation and motivational factors influencing the use of modern family planning methods including depot-medroxyprogesterone acetate subcutaneous (DMPA-SC). Methods Qualitative methods which include; Focus Group Discussions (FGDs) and In-depth Interviews (IDIs) were used to elicit information from women of reproductive age and gate-keepers in selected Nigerian states; Rivers, Ogun, Kwara, Niger, Anambra, Delta, Lagos, Enugu and Oyo. The categories of respondents include; unmarried women aged 18-25 years, women in union aged 18-24 years using modern family planning (FP), women in union aged 25-49 years using modern FP, women in union aged 26-49 years non-users of modern FP, community leaders, health facility focal person, husbands of current users of modern FP, husbands of non-users of modern FP, religious leaders, state FP coordinators and women aged 18-49 years who currently use DMPA-SC. Maximum variation sampling techniques was used to enlist participants to participate in both FGDs and IDIs. Results Respondents reported being motivated to use FP for reasons such as benefits of the method, economic situation, suitability of the methods, fear of unwanted pregnancy and its convenience. Further analysis showed that the unmarried respondents discussed more about fear of unwanted pregnancy and accessibility and affordability as a key motivator; while women in union discussed more on economic situations, encouragement from partners and benefits of FP when compared with the unmarried. In addition, respondents reported that their partners, health workers and friends influenced their decisions to use FP. Partners' encouragement, personal experience, accessibility and availability, awareness of FP and its benefits; willingness to space children and costs were notable enablers of FP use. The triggers for FP use were; appointment cards, phone calls from health workers, reminders (text messages, phone alarms and partners' support). Conclusion Increasing utilization therefore requires a well-planned horizontal approach that considers all enabling factors influencing utilization including women's empowerment. Family planning programmes that are client centered, address socio-cultural and gender norms and ensure access to contraceptive mix methods are recommended to improve utilization rate. This study recommends improved care-seeking behaviour through community-based awareness creation to address myths and misconceptions of family planning use, establishment of contraceptive delivery teams to prevent challenges of availability and accessibility, value clarification and tasks shifting among others to deal with the issue of inadequate family planning utilization.